2018
DOI: 10.1158/1538-7445.am2018-2440
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2440: Potentiation of the action of chemotherapeutic drugs by the hypoxia-activated prodrug SN30000 in multicellular tumor spheroids

Abstract: Introduction: Chemotherapy is often limited by resistant subpopulations of tumor cells. Tumor hypoxia contributes to resistance of tumor cells to clinical drugs via multiple mechanisms. Hypoxia-activated prodrugs selectively target hypoxic cells, among which SN30000 is a second generation of tirapazamine analogue with superior diffusion coefficient and hypoxia selectivity. Here we hypothesize that SN30000/chemotherapy drug combinations will provide improved activity. Methods: HCT116 and SiHa sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…However, one set of measurements of the SiHa spheroids was not sufficient to confirm the difference, but provided guidance for the rest of the study. Over days 4 to 7 of spheroid growth, the cells rapidly multiplied and the spheroids grew in size, as expected 15 . However, the spheroid RIs did not show a trend over that short period of time, which indicates the need for a longer longitudinal study.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…However, one set of measurements of the SiHa spheroids was not sufficient to confirm the difference, but provided guidance for the rest of the study. Over days 4 to 7 of spheroid growth, the cells rapidly multiplied and the spheroids grew in size, as expected 15 . However, the spheroid RIs did not show a trend over that short period of time, which indicates the need for a longer longitudinal study.…”
Section: Discussionsupporting
confidence: 72%
“…We have demonstrated that, after day 5, the core of the spheroid is not cellular, but consists of Hoechst 33342 staining cellular debris 15 . A perfect RI match enables no contrast with transmitted light microscopy with the spheroid appearing invisible.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The difference in the range of spheroid RIs between the pilot study SiHa and the HCT116 cells may be attributed to the fact that the characteristics of multicellular spheroids vary with the origin and type of cell line used 23,24 . However, one set of measurements of the SiHA spheroids was not sufficient to confirm the difference.…”
Section: Liu Et Al (mentioning
confidence: 99%